1985
DOI: 10.1044/jshd.5002.150
|View full text |Cite
|
Sign up to set email alerts
|

Oral Structural and Neuromuscular Characteristics in Children with Normal and Disordered Articulation

Abstract: The primary purpose of this study was to determine whether there were any signs of structural and/or neuromuscular aberrations in the speech mechanisms of children who were previously diagnosed as having "functional" articulation disorders. These children were compared with a group of normally articulating children. Results of in-depth oral mechanism examinations revealed no significant differences between these groups on any of the measures made. The clinical implications of such findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…This could also be observed in other studies [7,18,[21][22][23] , which indicates greater difficulty in quickly moving the back of the tongue in comparison with the tongue or lips. Results found for DDK of 'ka' corroborate the hypothesis of Cheng et al [26,27] , which states that the motor development of speech is not uniform and that there is a refining period starting from mid-childhood until adolescence.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This could also be observed in other studies [7,18,[21][22][23] , which indicates greater difficulty in quickly moving the back of the tongue in comparison with the tongue or lips. Results found for DDK of 'ka' corroborate the hypothesis of Cheng et al [26,27] , which states that the motor development of speech is not uniform and that there is a refining period starting from mid-childhood until adolescence.…”
Section: Discussionsupporting
confidence: 70%
“…Girls tend to be faster in the production of monosyllables and boys are faster in the repetition of polysyllables [18] . Differences were not found between genders in several studies of DDK in children [19,22,24,25] .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies of the link between oral motor skills and language have tended to look at simple movements more closely resembling eating movements (Moore & Ruark, 1996), or fast repeated movements (Dworkin & Culatta, 1985), neither of which seem to have a relationship with language development and disorders in these two studies. Our data suggest that more difficult oral movements are more closely related to language skills, possibly because they are more speech-like.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 155) A review of the studies since Winitz concluded that there is still no definitive answer to this question. Studies that treated this population as a single undifferentiated group (e.g., Dworkin & Culatta, 1985;Jordan, Hardy, & Morris, 1978;Qvarnstrom, Jaroma, & Laine, 1993) found both differences and no differences compared to typically developing children. Studies that compared subgroups of children with SD of unknown origin to each other or to typically developing children (e.g., Bradford & Dodd, 1996;Hamlet, 1985;Hetrick & Sommers, 1988;McGlone & Proffit, 1973) also revealed a mixed picture.…”
Section: The Speech-motor Deficit Hypothesismentioning
confidence: 99%